232 WORKING-UP DEMENTIA, A RETROSPECTIVE COHORT STUDY OF REFERRALS TO A SPECIALIST DEMENTIA SERVICE. (25th October 2022) - Loughlin, E; Gibbons, O; Burke, S; Okon, M; O'Sullivan, F; Drumm, B; O'Donnell, M; Patel, S; Hickey, P; McCarthy, G; O'Malley, G
Abstract: Background: Rates of dementia in Ireland are rapidly increasing in line with our ageing population. Cases are predicted to more than double in the next 30 years from a prevalence of 55, 000 in 2018, to 141, 000 in 2050. Dementia services will be placed under significant pressure. It is essential that patients referred to specialist memory services are appropriately worked-up prior to referral, to ensure efficiency and optimise the running of these services, and also to improve patient experience. Methods: We carried out a retrospective review of patients referred to the Psychiatry of Later Life Team for specialist dementia care by General Practitioners. We obtained date of referral to the service, and carried out an electronic chart review to evaluate the work-up performed prior to referral. Our standard work-up criteria consisted of neuroimaging (CT brain or MRI brain), and blood tests including B12, folate, and thyroid function tests within 12-months. Results were analysed descriptively. Results: 104 patients were included in the study, from referrals dated Nov 2014-June 2019. Neuroimaging had been performed in 79.8% (n=83) prior to referral- 89.1% CT, 9.6% MRI, 1.2% both CT and MRI. Of those who had neuroimaging, n=37 had been performed in the previous 12-months, representing 35.6% of overall cohort. In terms of blood work-up, 23.1% (n=24) had bloods performed in the 12 months prior to referral- 70.8% B12, folate and thyroid function tests; 20.8% TFTS only; 8.3% B12 and folate levels only). Conclusion: Referrals to specialist memory services by General Practice often lack the appropriate first line investigations, which introduces delay in review and the need for further assessment once baseline investigations have been done. There is a need for a standardised work-up prior to referral for optimum running of such services.